The role of agricultural sector performance in attracting foreign direct investment in the food and beverages sector. Evidence from planned investments in Africa - Zaneta Kubik (Agribusiness, 2023)
Using a novel dataset on foreign direct investment (FDI), this paper analyzes the correlates of planned FDI in the food and beverages sector in 49 African countries over the period 2003–2017. It applies the random effects model and augments the standard specification of FDI determinants with a set of factors related to the agricultural sector performance, hypothesized to be essential from the perspective of supply chain linkages and access to raw materials. The results indicate that well-performing and well-capitalized agricultural sector of the host country is a key factor associated with the choice of investment location by foreign investors, especially those from the Global North. Capital investment in agriculture, as proxied by agricultural gross fixed capital formation and net capital stock, is particularly important. Public investment in agriculture, in the form of government expenditure and official development assistance, is also associated with higher FDI. These factors, however, are not significant in case of the least developed countries where only market potential appears to matter for foreign investors. The results suggest that complementarities may exist between different types of investments and that policy-makers willing to attract food and beverages FDI should prioritize agricultural sector development.~[EconLit Citations: E22, E24, F21, F23, Q00, Q13, Q18].
Keywords: 630; Africa; agriculture; food; foreign direct investment